Rural digital economy drives rural industrial development through quality, efficiency, and dynamism transformations in China - Jia, Xingmei; Zhu, Tingting (Frontiers in Sustainable Food Systems, 2025)
As networking, informatization, and digitization become increasingly embedded in agriculture and rural economies, the digital economy is emerging as a key driver of rural industrial development. Drawing on data spanning from 2013 to 2023, this study employs an entropy-weighted methodology to quantify the levels of rural digital economy and rural industrial development. Through mediation and moderation effect models, the research explores the mechanisms by which quality, efficiency, and dynamism transformations mediate the role of the rural digital economy in driving rural industrial development. The findings indicate a significant positive impact of rural digital economy on rural industrial development, with the magnitude of influence diminishing sequentially from China’s central to western and eastern regions. Further analysis identifies quality, efficiency, and dynamism transformations as mediators, among which efficiency transformation exhibits the most pronounced mediating effect. Regional comparisons reveal that quality and dynamism transformations’ mediation effects diminish sequentially from western to central and then eastern regions, whereas efficiency transformation’s mediating role decreases from eastern to western and central regions, respectively. Regarding moderation effects, quality transformation prominently moderates in the eastern region, while efficiency and dynamic transformations are notably influential in the central region. Thus, the eastern region has transitioned into a high-quality development phase driven primarily by efficiency transformation, whereas central and western regions remain in phases characterized by scale expansion. Consequently, eastern regions should prioritize enhancing quality and efficiency through technological innovation and industrial upgrading to achieve superior quality and greater efficiency. Meanwhile, central and western regions should emphasize the synergistic effects of efficiency and dynamism transformations by optimizing resource allocation, boosting productivity, and invigorating market vitality to foster sustainable rural industrial development.